Infection Clostridium difficile as increasing epidemiological issue - Rutkowski, Maciej; Roszkowska, Anna; Swierszcz, Lukasz; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2017)
Abstract Introduction: Clostridium difficile as an infectious agent of pseudomembranous enterocolitis, becomes more and more frequent problem among health facilities. Dread disease and its complications can be fatal, especially in elderly and infant group. Epidemiological analysis enables to highlight validity and importance of this issue in, and submit it to National Health Service. The aim of the study is to show current epidemiological status concerning Clostridium difficile frequency in Poland for recent years. Materials and methods: Data used for the epidemiological analysis was taken from reports of National Hygiene Institute such as „Choroby zakaźne i zatrucia w Polsce” and „Zakażenia Clostridium difficile” prepared by NPOA (Narodowy Program Ochrony Antybiotyków). Results and conclusion: The level of Clostridium difficile infections is alarmingly high. Health facilities should remain alert regarding the rate of carrier state among infant and hospitalized group especially because of complications risk. Therefore, hygiene and aseptic conditions in medical institutions should be emphasised as well as appropriate antibiotic therapy.